Temporal and inter-species variations in the proximate and contaminant compositions of farmed mussels, Choromytilus meridionalis and Mytilus galloprovincialis, from Saldanha Bay, South Africa - Firth, Deborah Caitlin (Stellenbosch : Stellenbosch University, 2018)
Thesis (MScAgric)--Stellenbosch University, 2018.